Meiotic chiasmata variations in the H genome among Triticeae species of varying ploidy - Yang, Ying; Liu, Bo; Chen, Jie; Guo, Jialei; Shen, Wenjie; Meng, Yixin; Dou, Quanwen (Frontiers in Plant Science, 2025)
Meiotic chiasmata are critical for genetic diversity and chromosome segregation. This study aimed to cytologically analyze the variations in chiasmata within the H genome across different ploidy levels, specifically in diploid (Hordeum bogdanii), autotetraploid (Hordeum brevisubulatum), and allotetraploid (Elymus sibiricus) species, to understand the impact of polyploidization. We conducted a comparative cytological analysis of meiotic chiasmata in the H genome of the three species during diakinesis and metaphase I. This study revealed significant variations in the types and frequencies of chromosomal pairing configurations both across different species and among chromosomes within the same species. H. brevisubulatum exhibited a high frequency of quadrivalents. The number of chiasmata in the H genome decreased from 21.32 in H. bogdanii to 19.00 in E. sibiricus and 14.67 in H. brevisubulatum per genome during diakinesis, with a further significant reduction observed at metaphase I. All chromosomes exhibited a similar reduction in chiasmata number from diploid to tetraploid, with the exception of chromosome 1H, which showed a significant increase in E. sibiricus during diakinesis. The frequency of chiasmata significantly decreased from H. bogdanii to E. sibiricus and H. brevisubulatum in both the terminal and interstitial regions. Chiasmata in E. sibiricus and H. brevisubulatum were more terminally localized compared to those in H. bogdanii. However, a significant increase in chiasmata frequency was observed on the short arms of chromosomes 1H and 4H in E. sibiricus during diakinesis. Various patterns of chiasmata localization were observed across the three species during diakinesis. In E. sibiricus, interstitial chiasmata were distributed more distally along both chromosomal arms compared to those in H. bogdanii. In contrast, interstitial chiasmata were absent on the short arms of most chromosomes in H. brevisubulatum and exhibited a more proximal distribution on the long arms. The evolutionary and adaptive significance of these chiasmata variations during polyploidization was further discussed.